Impact of Water Supplementation With Turmeric and Tamarind Extracts on Broiler Liver Performance - Sudatri, N.W.; Suartini, N.M.; Dewi, G.A.M. Kristina; Mahardika, I G.; Bidura, I G.N. Gde (KnE Life Sciences, 2022)
Turmeric and tamarind are medicinal plants that have a variety of health benefits, including laxative, antibacterial, anticancer, and hepatoprotective properties. The focus of this research was to look at the histology of the liver and the levels of SGPT-SGOT in broilers fed turmeric-tamarind extracts water at a rate of 2%. This study used a completely randomized design, with treatment options including a control, a mixture of turmeric rhizome and tamarind fruit (2%), and concentrations of 2% turmeric rhizome and 2% tamarind. The turmeric rhizome and tamarind extracts treatment was given in drinking water ad libitum. Quantitative data from the study were analyzed statistically, and if there was a significant effect, Duncan’s test was used; qualitative data were presented with descriptions and images. The blood levels of SGPT in the control broilers were higher than in the broilers exposed to any of the other treatments. Also, in the control broiler livers, hydrofic degeneration, nucleus pyknosis, and congestion were higher than in the treatment group broilers, but these were still within normal limits. Water supplementation with a mixture of turmeric rhizome and tamarind fruit extracts did not have a negative effect on the performance of the broiler livers. Keywords: turmeric, tamarind, liver performance, broiler